2002
DOI: 10.1007/s00018-002-8448-0
|View full text |Cite
|
Sign up to set email alerts
|

The interleukin-10 - 1082 G/A polymorphism: allele frequency in different populations and functional significance

Abstract: Genotypic variation in the human interleukin-10 (IL-10) promoter may account for marked inter-individual variation in IL-10 production and may influence susceptibility to autoimmune diseases. The G/A polymorphism at position -1082 has been linked to high/low IL-10 producer status. We directly tested the functional significance of this polymorphism using DNA-binding assays and reporter gene assays, examined allele frequencies in two geographically distinct populations and assessed intra- and inter-individual va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 24 publications
2
68
0
3
Order By: Relevance
“…19,20,26,27,32 The present series of experiments were performed to study the influence of the binding of the Sp1 transcription factor to the À1087 SNP on IL-10 transcription. The binding of the transcription factors PU.1, Spi-B and Sp1 to this site in the IL-10 promoter was earlier analyzed using electromobility shift assay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20,26,27,32 The present series of experiments were performed to study the influence of the binding of the Sp1 transcription factor to the À1087 SNP on IL-10 transcription. The binding of the transcription factors PU.1, Spi-B and Sp1 to this site in the IL-10 promoter was earlier analyzed using electromobility shift assay.…”
Section: Discussionmentioning
confidence: 99%
“…19,[25][26][27]32,40,41 Thus, Turner et al 27 found that subjects who were negative for the A allele exhibited a higher production of IL-10 than subjects who were positive for the A allele. These results are in concordance with data presented in a study on stimulated purified blood lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the presence of an A-allele was shown to result in an increase in the IL-10 promoter activity, which may lead to enhanced production of the IL-10 protein. 23 Conversely, other reports suggested that the presence of a G-allele at À1087 was associated with an increase in the IL-10 promoter activity. 24,25,28,29 In earlier studies from our laboratory, 30,31 we demonstrated that severe chronic periodontitis was strongly associated with the GG genotype of the À1087 IL-10 gene polymorphism and that the GG genotype correlated with enhanced fractions of IL-10-positive cells in periodontitis lesions.…”
Section: Introductionmentioning
confidence: 97%
“…[20][21][22] The IL-10 promoter contains several single nucleotide polymorphisms (SNPs) among which the -1087 G/A SNP (sometimes referred to as À1082 G/A) was associated with differences in IL-10 promoter activity and IL-10 production. [23][24][25][26][27][28][29] Results of studies on the influence of the -1087 SNP on the IL-10 production in different cell types, 23,[25][26][27][28][29] however, are conflicting. Thus, the presence of an A-allele was shown to result in an increase in the IL-10 promoter activity, which may lead to enhanced production of the IL-10 protein.…”
Section: Introductionmentioning
confidence: 99%